Integralisme Islam dan Nilai-nilai Filosofis Budaya Lokal pada Pembangunan Propinsi Lampung - Fauzie Nurdin, A. (Unisia, 2012)
This research elaborates on the Islamic integralism and local cultures, focusing on the relevance of philosophy of Lampung culture for the development of Pesawaran. Cultural philosophical approach is used to explain problems that have to be understood and realized in daily life. The methods used are participatory observation, in-depth interview, and document study. Qualitative analysis of philosophy is used to interpret and compare and correlate theory with the processed and applied data. This research reveals that the Islamic integralism and the philosophical values of local cultures are contained in Lampung culture, having been the facts and works of the actors. Thus, Piil Pasenggiri as philosophy of life has grown up in the society as ‘local genius’ and ‘local wisdom’ of the nation, useful for regional development. Keywords: Islamic integralism, local culture, Piil Pesenggiri, regional development.